2018
DOI: 10.1002/ptr.6035
|View full text |Cite
|
Sign up to set email alerts
|

Superior anticancer activity is demonstrated by total extract of Curcuma longa L. as opposed to individual curcuminoids separated by centrifugal partition chromatography

Abstract: Three curcuminoids: bisdemethoxycurcumin, demethoxycurcumin, and curcumin from turmeric were successfully separated by a high capacity solvent system composed of heptane: chloroform: methanol: water mixture (5: 6: 3: 2 v/v/v/v) tailored for centrifugal partition chromatographs at K-values of 0.504, 1.057, 1.644, respectively. These three ferulic acid derivatives obtained at a purity rate exceeding 95% were analysed by an HPLC-MS spectrometer. Turmeric extract inhibited the proliferation/viability of A549 human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
28
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 32 publications
2
28
0
3
Order By: Relevance
“…Turmeric, Curcuma longa L., is a well‐known herb of the Zingiberacea family and a natural colorant. As the main component of Curcuma longa L, curcuminoids have been explored in antiprotozoal [1], antioxidant [2], anticancer [3–5], preventing diabetic nephropathy [6], and preventing Alzheimer's disease [7]. Curcumin (CC), demethoxycurcumin (DMCC), and bisdemethoxycurcumin (BDMCC) are the three main curcuminoids (Figure 1A), and CC is the most important active component [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Turmeric, Curcuma longa L., is a well‐known herb of the Zingiberacea family and a natural colorant. As the main component of Curcuma longa L, curcuminoids have been explored in antiprotozoal [1], antioxidant [2], anticancer [3–5], preventing diabetic nephropathy [6], and preventing Alzheimer's disease [7]. Curcumin (CC), demethoxycurcumin (DMCC), and bisdemethoxycurcumin (BDMCC) are the three main curcuminoids (Figure 1A), and CC is the most important active component [8].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, CCC has been already successfully used in the purification of phytosterol [17], fatty acids [18], anthocyans [14], polyphenols [19], flavones [20], and many other natural and synthetic products [21]. It has been reported that CC could be separated by counter‐current chromatography [22] or centrifugal partition chromatography [5], but the solvent system contains chloroform that is forbidden in China. Recently, with the development of counter‐current chromatography technology, a new high‐performance counter‐current chromatography (HPCCC) equipment with higher separation efficiency has been developed [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely used for therapeutic purpose histologically due to the intrinsic anti‐inflammatory, antioxidant and antitumour properties . The extensive investigations and exploitations have characterized the wide‐spectrum anticancer activity of curcumin against variety of human tumours including ovarian, breast, colon and so forth . The various modes of action have been proposed underlying its therapeutic function in treatment of human cancer, including inhibition of proliferation, induction of cell apoptosis and suppression of angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19] The extensive investigations and exploitations have characterized the wide-spectrum anticancer activity of curcumin against variety of human tumours including ovarian, breast, colon and so forth. [20][21][22][23][24][25] The various modes of action have been proposed underlying its therapeutic function in treatment of human cancer, including inhibition of proliferation, induction of cell apoptosis and suppression of angiogenesis. However, the potential antitumour effect of curcumin against ESCC has not been extensively explored despite the sporadic reports conducted in immortalized human cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…The preclinical studies included in the present virtual issue give further insights into the molecular mechanisms of curcumin in diabetes (Gutierres et al, ), depression (Abd‐Rabo, Georgy, Saied, & Hassan, ), wound healing (Yang et al, ), kidney diseases (Russo et al, ), antibiotic therapy (Marini et al, ), and in carcinogenesis (Javadi, Rostamizadeh, Hejazi, Parsa, & Fathi, ; Kukula‐Koch et al, ; Schmidt et al, ; Tseng, Chiou, Weng, & Lin, ), a topic extensively covered in our Journal (Abbaszadeh, Keikhaei, & Mottaghi, ; Asemani, Zamani, Bayat, & Amirghofran, ; Hosseinabadi et al, ; Kundu, Das, Dhara, & Mandal, ; Salehi et al, ; Wattanathamsan, Hayakawa, & Pongrakhananon, ). Finally, a study in the rat (Dogra et al, ) highlighted the potential risk of interaction between curcumin and daclatasvir, a selective hepatitis C virus, nonstructural Protein 5a polymerase replication complex inhibitor.…”
mentioning
confidence: 99%